Rancang Bangun Alat Pulse Oximeter Portabel Berbiaya Rendah Berbasis IoT - Indri Desriani; Mona Berlian Sari (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2026)
Real-time monitoring of heart rate and oxygen saturation is commonly performed using conventional medical devices that are impractical for daily use. This study aims to design a low-cost, Internet of Things (IoT)-based portable pulse oximeter prototype for real-time health monitoring. The system employs a MAX30100 sensor to measure BPM and SpO₂, an ESP32 microcontroller for data processing, and an OLED to display the results. The measured data are also transmitted to the Blynk application for remote smartphone monitoring. Performance was evaluated on 20 participants consisting of 10 men and 10 women, by comparing the measurement results with those of the commercial Serenity OX-48 pulse oximeter. System performance was assessed using accuracy, Mean Absolute Error (MAE), standard deviation, and Pearson correlation. The male group achieved an average accuracy of 98.71% for BPM (MAE = 1.09 BPM; r = 0.99) and 99.16% for SpO₂ (MAE = 0.80%; r = 0.92). Meanwhile, the female group achieved an average accuracy of 98.88% for BPM (MAE = 1.01 BPM; r = 0.99) and 99.17% for SpO₂ (MAE = 0.80%). These results indicate that the system delivers accurate, stable, and reliable measurements and is suitable for real-time IoT-based physiological monitoring.